2004
DOI: 10.1021/bi035432b
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Binding Properties and Conformational States of Calcium- and Integrin-Binding Protein

Abstract: Calcium- and integrin-binding protein (CIB) is a novel member of the helix-loop-helix family of regulatory calcium-binding proteins which likely has a specific function in hemostasis through its interaction with platelet integrin alphaIIbbeta(3). The significant amino acid sequence homology between CIB and other regulatory calcium-binding proteins such as calmodulin, calcineurin B, and recoverin suggests that CIB may undergo a calcium-induced conformational change; however, the mechanism of calcium binding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
113
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(131 citation statements)
references
References 53 publications
15
113
2
Order By: Relevance
“…Ca 2ϩ induces a conformational change in CIB1 (17) and modulates the binding and regulatory actions of CIB1 on several CIB1-interacting proteins (18,30). In the present study, the binding of CIB1 to ASK1 was blocked either by ionomycin (Fig.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Ca 2ϩ induces a conformational change in CIB1 (17) and modulates the binding and regulatory actions of CIB1 on several CIB1-interacting proteins (18,30). In the present study, the binding of CIB1 to ASK1 was blocked either by ionomycin (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Although it was initially discovered in platelets as a protein that interacts with integrin ␣ IIb (11), CIB1 also binds many other proteins including presenilin 2, DNA-dependent protein kinase, the polo-like kinases Fnk and Snk (14)(15)(16). Furthermore, the binding of Ca 2ϩ to CIB1 induces conformational changes that modulate the interaction with at least some of its binding proteins (17). CIB1 is widely expressed among tissues (18) and is likely to play a role in various cellular processes.…”
mentioning
confidence: 99%
“…Sample Preparation-The CIB1 protein was prepared as described previously (17). The 13 C, 2 H, 15 N-uniformly labeled sample was expressed and purified according to an established protocol (12), and this sample was used to acquire the backbone 1 7 -glucose; this sample was used to record the CIB1 backbone CPMG-relaxation dispersion spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Because the magnesium ion is constantly present in the cytosol in millimolar concentrations, the magnesium-bound form of CIB1 (Mg 2ϩ -CIB1) is considered to be the physiologically relevant form of CIB1 in the resting state of the cell (17). CIB1 has been found to bind Mg 2ϩ only at its EF-III site, but it still possesses an overall well folded tertiary structure (17 ther suggested that Mg 2ϩ -CIB1 and Ca 2ϩ -CIB1 have similar tertiary structures with subtle differences (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation